Prevalence of anxiety and depression among Lebanese women using oral contraceptives: a cross-sectional study - Kamel Jaafar; Elias Nabhan; Rama Daoud; Zeina Nasser (BMC, 2024)
Abstract Background Oral contraceptives (OCs) are used worldwide, including Lebanese women. However, the association between OCs use and anxiety or depression remains unclear. This study aims to assess the prevalence of anxiety and depression among Lebanese women using oral contraceptive pills and investigate the differential impact of combined oral contraceptives (COCs) versus progestogen-only pills (POPs) on mental health outcomes. Methods A cross-sectional study was conducted among a sample of Lebanese women using OCs between January and March 2023. Nine hundred nighty seven out of the 2051 women who took part in the survey met our criteria and were included in this study. Data on anxiety and depression were collected using validated and reliable scales, the Arabic versions of the Generalized Anxiety Disorder-7 Questionnaire (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9). Statistical analyses, including multivariate analysis, were performed to assess the association between OCs type (COC vs. POP) and anxiety/depression. Results The prevalence of anxiety and depression among Lebanese women taking OCs was found to be 39.9% and 64.3%, respectively. Furthermore, the study revealed that POP users had 2.8 times higher odds of developing anxiety (adjusted odds ratio ORadj = 2.8 with 95% confidence interval CI of 1.770 to 4.435) p-value < 0.001 and 9.2 times higher odds of developing depression (adjusted odds ratio ORadj = 9.2 with 95% confidence interval CI of 5.790 to 14.506) p-value < 0.001 compared to COC users. Conclusion The results of this study shed light on the elevated prevalence of anxiety and depression among Lebanese women using OCs and emphasized the varying effects of COCs and POPs on their mental health outcomes. Further research is needed to comprehensively understand this association, considering both the dosage and specific type of oral contraceptive to improve the overall well-being of women using these contraceptives.